Differences in sounds made by courting males of three closely related Lake Malawi cichlid species - Amorim, Maria Clara Pessoa (2012)
Courtship sounds made by three sympatric cichlid species, Pseudotropheus zebra, P. callainos and an undescribed species known as P. ‘zebra gold’ were recorded and compared to investigate the potential role of acoustic signals in mate choice. Sounds were emitted during ‘quiver’ and ‘circle’ components of the male courtship display and consisted of rapidly repeated pulse units. Some sound variables differed significantly among species with P. callainos generally being separated from the other two species. This species produced sounds with higher peak frequency (for a given length) and lower number of pulses than P. ‘zebra gold’ and higher pulse durations than P. zebra. In addition, standard length was inversely related to peak frequency in both P. ‘zebra gold’ and P. callainos (this relation was not tested in P. zebra due to the small sample size). These differences might indicate different regimes of intraspecific sexual selection among the three species.